The utilization of information and communication technologies by local government in social policy applications: The example of implementation in municipalities of the Epirus region - Daflou, Ekaterini (The Greek Review of Social Research, 2019)
The doctoral dissertation presented was prepared by the Department of Social Policy, Panteion University School of Political Science. According to the committee resolution, the dissertation was approved in October 2016. The committee was consisted of the primary supervisor Professor A. Moissidis and two committee members, from the Technical University of Athens Professor I. Kalogirou (committee member) and from Panteion University Assistant Professor K. Dimoulas (committee member). The doctoral dissertation examines the problem of locality through social policy practice.